Implementasi Pendidikan Karakter terhadap Prestasi Belajar Siswa di MTs Al-Islahiyah Bobosan Kandangan Kediri - Izza Munawar (LPPM IAI Hasanuddin Pare-Kediri, 2017)
Character education is a very important factor in achieving learning goals, because with a good character education will create a condition learning efficient and effective. If the process of character education in learning activities can be run well, it will support student achievement in reaching the desired educational goals. The research goal of this thesis are: 1) To determine the purpose and methods of character education. 2) To examine the MTs.Al-Islahiyah Bobosan efforts in implementing character education 3) To determine the increase learning achievement after that character education is implemented. This study used a qualitative approach, which is a research procedure that produces descriptive data in the form of speech or spoken of the observable behavior of the subject itself. Data was obtained through interviews, observation, and documentation will be continued with the analysis of data by reviewing all data have been obtained. Data analysis includes data presentation, data reduction, and conclusion. The conclusion of this study were: 1) the character education in MTs. Al-Islahiyah Bobosan Kemiri Kandangan Kediri. In character education in schools, all components must be involved, including the educational components itself, namely, curriculum, teaching, building infrastructure, teachers and students. 2) As for character education is applied in MTs. Al-Islahiyah, namely: read juz 'amma and asmaul khusna, Pray Duha, midday prayer, fasting Monday and Thursday, istighosah, honesty or trustworthy, respectful and polite, generous and love helping. The factors supporting character education, namely: curriculum, infrastructure classes, teachers, pupils and the surrounding environment. 3) The learning achievement in MTs. Al-Islahiyah Bobosan was relatively well attested by the value UASBN, UAS, as well as the Championship Achievement Achievement value of report cards.